The ELAStiC (Electronic Longitudinal Alcohol Study in Communities) project. (2017) - Akbari, Ashley; Lyons, Ronan; Berridge, Damon; Gallacher, John; MacLeod, John; Heron, Jon; Hickman, Matthew; Mahedy, Liam; Bellis, Mark; Fone, David; Paranjothy, Shantini; Trefan, Laszlo; et al.
No abstract available